Understanding early uptake of PrEP by female sex workers in Zimbabwe. Issue 6 (3rd June 2021) - Busza, Joanna; Phillips, Andrew N.; Mushati, Phillis; Chiyaka, Tarisai; Magutshwa, Sitholubuhle; Musemburi, Sithembile; Cowan, Frances M.
ABSTRACT: Female sex workers (FSW) are prioritised for increased access to pre-exposure prophylaxis (PrEP), although rates of uptake remain sub-optimal, particularly across Southern Africa. In the first two years of its availability in Zimbabwe, 37.1% of FSW in trial sites initiated PrEP and received at least one re-supply. We conducted a qualitative study on perceptions of PrEP among 19 early users selected from sites with varying rates of PrEP initiation. Narrative interviews examined the pathways taken by FSW from hearing about PrEP, through their decision to start taking it, and early experiences. FSW appreciated PrEP's introduction within familiar and trusted "friendly" services tailored for sex workers and valued positive encouragement from clinic staff and peers over negative influence from family members. They also found PrEP difficult to understand at first, and feared side effects and rare adverse complications described in information leaflets. While FSW identified individual strategies for remembering to take their medication, they also relied on structured peer adherence support, leading some FSW to actively promote the method to other FSW as "PrEP champions". Information on how early users experience a new prevention technology such as PrEP can inform design of interventions that leverage existing support structures and target key barriers.